Post-alcoholic hypoglycaemia: a clinical and pathological study - Naeme, Peter Brereton (Department of Medicine, 2020)
For a number of years a history of sudden onset of coma, followed later by death, was noted amongst Africans at King Edward VIII hospital, Durban. Necropsy, where performed, revealed no cause in many of these patients. In 1957 after cerebrospinal fluid had been examined in some of the cases it was seen that the only abnormality present was a low cerebrospinal sugar. Hypoglycaemia was suspected and blood sugar estimation confirmed it. Further investigation failed to reveal the cause of the hypoglycaemia and in some cases because of a "flat" glucose tolerance curve organic hyperinsulinism was suspected. In one case total pancreatectomy was performed but thorough macroscopical and histological investigation failed to reveal a tumour or hyperplasia, and the patient subsequently suffered from diabetes. In August 1958, I admitted an African female patient, of 26 years, to the ward in coma.